Literature Review on the Fatigue Properties of Materials Processed by Surface Mechanical Attrition Treatment (SMAT) - Pengfei Gao; Zhidan Sun; Delphine Retraint (Metals, 2022)
As a promising surface treatment technique, the surface mechanical attrition treatment (SMAT) has been applied to enhance mechanical properties of various materials. Through multidirectional severe plastic deformation, SMAT is able to nanocrystallize the near surface region of materials. The nanostructured layer associated with high compressive residual stresses coupled with a work hardening layer can provide the treated materials with an improved fatigue resistance. The present work gives a comprehensive review on the fatigue strength of SMATed materials. First of all, a brief introduction is given on the basic elements of SMAT and surface modifications induced by this treatment. The fatigue strength of a large variety of SMATed materials with different loading conditions is reviewed, including low-cycle fatigue (LCF), high-cycle fatigue (HCF) and very-high-cycle fatigue (VHCF). Then, the mechanism of enhancement or reduction is explained through a detailed review on the effects of several factors, such as residual stress, surface quality and nanocrystalline grains. In addition, the combined effect of SMAT coupled with other processes is also reviewed. Trends and prospects of the current research are summarized at the end.